El enfoque de Ciencia, Tecnología y Sociedad en el proceso de enseñanza-aprendizaje de la asignatura Química Orgánica - Martínez Olmo, MSc. Yanelain; Padilla Gómez, MSc. Annette (Revista Conrado, 2017)
Desde el proceso de enseñanza-aprendizaje de la Química Orgánica se intenta contribuir a la comprensión del significado social de la ciencia y la tecnología por medio de la inclusión de las consecuencias en el método de estudio de análisis de los contenido, a través de la idea rectora estructura-propiedad-aplicación, como expresión de la transformación del cuadro científico del mundo que ha sido construido a partir del conocimiento adquirido en la actividad cognoscitiva, la percepción de la experiencia y la práctica histórico-social de la actividad de los hombres. Las potencialidades del contenido para el análisis social enfatizan lo ambiental, para desarrollar así, una cultura científica y tecnológica en el proceso de enseñanza–aprendizaje de esta ciencia teórica-experimental. Palabras clave: Ciencia, tecnología, cultura científico, química orgánica, conocimiento pertinente, cuadro científico. ABSTRACT The scientific and technological perspective must be treated from the process of formation when establishing the relationships of the systems of knowledge in the subject Organic Chemistry with a social approach, which reveals the links between science- technology and society in order to continue the quest of an integrating view of the world. The Organic Chemistry, from the Teaching-Learning process, attemps to make a contribution in the social meaning of the science and the technology by means of the inclusion of the consequences in the study of analysis of the contents method through the leading idea structure-property-application, as an expression of the world´s transformation of the scientific framework, which has been built from the acquired knowledge in the cognitive activity, the perception of the experience and the social-historic activity of humans. The potentialities of the content for the social analysis emphasize the environmental, with the aim of developing a scientific and technological culture in the teaching-learning process of this theoretical-experimental science. Keywords:Science, technology, scientific culture, Organic Chemistry, pertinent knowledge, scientific framework.